2011
DOI: 10.1002/jclp.20803
|View full text |Cite
|
Sign up to set email alerts
|

Training competent psychologists in the field of child maltreatment

Abstract: Child maltreatment is a serious threat to children's physical and psychological well-being; therefore, it is critically important to develop high-quality educational programs to train psychologists in effectively addressing child abuse and neglect. Various health care disciplines and areas within the field of psychology have established competencies as a guide for student training curricula; however, none have been established for the area of child maltreatment. The present article presents training competenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Even when cases are reported, many child welfare workers are not adequately trained to manage the cases. Further, research has shown that there is little specialized coursework in the area of child maltreatment and child advocacy, as well as a lack of information on how to work together in as an effective team (Damashek, Balachova, & Bonner, 2011;Vieth, 2006). The team is an integral part of the Children's Advocacy Center (CAC) model that was created in the early 1980s by Congressman ''Bud'' Cramer in Huntsville, Alabama.…”
Section: Introductionmentioning
confidence: 97%
“…Even when cases are reported, many child welfare workers are not adequately trained to manage the cases. Further, research has shown that there is little specialized coursework in the area of child maltreatment and child advocacy, as well as a lack of information on how to work together in as an effective team (Damashek, Balachova, & Bonner, 2011;Vieth, 2006). The team is an integral part of the Children's Advocacy Center (CAC) model that was created in the early 1980s by Congressman ''Bud'' Cramer in Huntsville, Alabama.…”
Section: Introductionmentioning
confidence: 97%
“…Child maltreatment is a serious threat to children's physical and psychological well-being (Damashek, Balachova, & Bonner, 2011). Child maltreatment can result in significant longterm emotional and behavioral consequences, including posttraumatic stress disorder (e.g., Dubner & Motta, 1999), aggression and anger (Shields, Cicchetti, & Ryan, 1994;Korkut, 2011;Taner & Gokler, 2004;Chapple, Tyler, & Bersani, 2005), school difficulties (Erickson & Egeland, 2002), depression (Boney-McCoy & Finkelhor, 1996), social difficulties (Mannarino & Cohen, 1996), criminal behavior (Gelles & Straus, 1990), low life satisfaction (Korkut, 2012) and self esteem (Bagley, Bolitho, & Mallick, 2001;Baldry, 2003;Durmuşoğlu & Doğru, 2006;Korkut, 2012) and long-term health problems (Anda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there appears to be little training in traumatic stress in graduate level education across mental health disciplines, resulting in calls for inclusion of this topic in psychology training programs (e.g., Courtois & Gold, 2009). This echoes earlier calls for graduate psychology training in specific types of trauma (Alpert & Paulson, 1990;Damashek, Balachova, & Bonner, 2011;Layne et al, 2011).…”
mentioning
confidence: 98%